The characteristics on structural and optical of Co3O4 incorporated Zn2SiO4 for phosphor approaches - Cheong, Wei Mun; Wei, Loh Zhi; Mohd Zaid, Mohd Hafiz (Elsevier, 2022)
The melt-quenching method was used to fabricate a series of cobalt oxide (Co3O4) incorporated ZnO-SLS with the empirical formula (Co3O4)0.01 (SLS0.5 ZnO0.5)0.99 in weight percent. The glass samples went through a heat treatment process to transform into zinc silicate (Zn2SiO4) glass-ceramics. The impacts of heat treatment duration on structural and optical properties were investigated. X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) confirmed the appearance of α- Zn2SiO4 peaks. Optical absorption occurs in the UV zone at wavelengths between 500 and 700 nm. The transition of Co2+ was discovered from 4A2 (F) → 4T1 (P). The optical energy band gap narrowed as the heat treatment duration increased. Co3O4-doped samples were found in the blue area of CIE chromaticity coordinates. The findings indicate Co3O4-doped Zn2SiO4 has the potential as a blue phosphor in the optoelectronic device.